2018
DOI: 10.1111/ans.14395
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early antiplatelet therapy after splenectomy with gastro‐oesophageal devascularization

Abstract: BackgroundThis study aimed to explore the effects of early antiplatelet therapy (APT) for portal vein thrombosis (PVT) in patients with cirrhotic portal hypertension after splenectomy with gastro‐oesophageal devascularization.MethodsWe retrospectively analysed 139 patients who underwent splenectomy with gastro‐oesophageal devascularization for portal hypertension due to cirrhosis between April 2010 and December 2016. Based on the post‐operative platelet values, we used two different APT regimens: APT was start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…A prospective study revealed that anticoagulant drugs significantly decreased the occurrence of PVST in cirrhotic patients with PH after splenectomy [ 30 ]. Aspirin combined with dipyridamole has also been proven safe and effective for the early prevention of PVST [ 31 ]. A previous meta-analysis suggested that low-molecular-weight heparin in conjunction with low-molecular-weight dextran is the most effective treatment for preventing PVST after splenectomy in cirrhotic patients [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study revealed that anticoagulant drugs significantly decreased the occurrence of PVST in cirrhotic patients with PH after splenectomy [ 30 ]. Aspirin combined with dipyridamole has also been proven safe and effective for the early prevention of PVST [ 31 ]. A previous meta-analysis suggested that low-molecular-weight heparin in conjunction with low-molecular-weight dextran is the most effective treatment for preventing PVST after splenectomy in cirrhotic patients [ 32 ].…”
Section: Discussionmentioning
confidence: 99%